The Role of Financial Behavior in Improving Investment Decision: Empirical Evidence of The Students of Economics and Business Faculty UPN “Veteran” Jawa Timur - Delvia Istiana; Dhani Ichsanuddin Nur (Journal of Economics, Business, and Government Challenges, 2020)
Financial behavior can understand the behavior of investors in making investment decisions. Investment decision making is a process of selecting the best alternative from a number of alternatives that are available under the influence of complex situations. Investment decision making is influenced by several factors, namely Anchoring Bias, Loss Aversion, and Overconfidence. The purpose of this research is to examine the contribution of Anchoring Bias, Loss Aversion, and Overconfidence of Active Students in the Faculty of Economics and Business UPN “Veteran” East Java as investors in improving investment decision making. The sampling technique used was purposive sampling with the sample determination technique using the Slovin formula. This study used 99 investor respondents who had invested more than three months and were active students of the Faculty of Economics and Business, UPN "Veteran" East Java. The data collection technique used a questionnaire which was then analyzed using a quantitative descriptive method with the Partial Least Square (PLS) model. The results of this study indicate that Anchoring Bias can contribute to improving investment decision making, Loss Aversion can contribute to improving investment decision making, and Overconfidence can contribute to improving investment decision making